Birdwatching Philippines a bird-learning mobile application that simplifies bird identification and showcases the diversity of birds in the Philippines - Gonzales, Johanna B.
The Philippines has the highest concentration of bird endemism in the world. However, most Filipinos seem to take it for granted. Despite the diversity of the birds in this country, the BIrdwatching activity is still unknown to majority of the locals. Moreover, there is no tool available today to quickly identify Philippine bird species. Mediums such as books and the internet are reliable sources of bird information but there are issues when it comes to the accessibility of field guides, ergonomics while birding, and accuracy in identification. With these taken into consideration, the researcher came up with the problem of how can a better understanding of Philippine birds be reinforced among Filipinos through visual communication.